Perioperative management of Endocrine disorders- practical considerations - Rizwan, Azra (Journal of the Pakistan Medical Association, 2025)
It is important to correctly identify and treat endocrine conditions well before, during and proceeding surgery, even if this entails delaying surgical intervention. Failure to do this has been shown to increase mortality and morbidity. Hormones are involved in controlling metabolism, cellular processes, blood pressure, blood glucose levels, calcium homeostasis as well as fluid and electrolyte balance. Disordered hormonal production can be deleterious right from the time of anaesthesia induction. Specific endocrine disorders, such as thyroid disorders, pheochromocytoma, Cushings, adrenal insufficiency, acromegaly, hypercalcemia, carcinoids and diabetes insipidus have been discussed in literature, with practical considerations. This includes alternative modality of drug administration, management of associated comorbidities, as well as optimisation of nutrient levels pivotal to the success of bariatric surgery. For the current narrative review, a search on Google, PubMed, Up-to-Date and relevant clinical practice guidelines was carried out to extract the requisite information. Optimisation of the endocrinopathy and its sequelae, geared towards achieving metabolic control starting well before the procedure, is likely to lead to good surgical outcomes. Key Words: Thyroid disorders, Pheochromocytoma, Cushings, Acromegaly, Hypercalcaemia, Hypocalcaemia, Carcinoids, Diabetes insipidus, Bariatric surgery.